Social support from family and friends for physical activity in adolescence: Analysis with structural equation modeling Apoio social de familiares e amigos para atividade física em adolescentes: Análise com modelagem de equações estruturais Apoyo social de la familia y amigos para la actividad física de adolescentes: Análisis con modelos de ecuaciones estructurales - Lisboa T.* (2021)
© 2021 Fundacao Oswaldo Cruz. All rights reserved.Social support is an important predictor for the maintenance of physical activity in adolescence. Thus, the social-ecological approach values the impact of individuals or groups interaction with available resources in the social environment for adopting an active lifestyle. This study analyzes social support from family and friends for adolescents to practice physical activity. Guided by the Social-Ecological Theory, an observational cross-sectional structural equations modeling was applied to 2,710 Brazilians adolescents aged from 14 to 18 years. We identified that the greater the social support from friends (β = 0.30; RMSEA = 0.065; CFI = 0.953; TLI = 0.922; SRMR = 0.048) and family, the greater the adolescents physical activity (β = 0.27; RMSEA = 0.015; CFI = 0.997; TLI = 0.995; SRMR = 0.013). However, support from both sources indicated no adequate adjustment values in the same study model. Our findings suggest that adolescents who perceive social support from family members or friends practice more physical activity, confirming that social support is important for physical activity promotion.